Probiotic mediated intestinal microbiota and improved performance, egg quality and ovarian immune function of laying hens at different laying stage - Xu, Hengyong; Lu, Yuxiang; Li, Dan; Yan, Chaoyang; Jiang, Yuru; Hu, Zhi; Zhang, Zhipeng; Du, Ranran; Zhao, Xiaoling; Zhang, Yao; Tian, Yaofu; Zhu, Qing; et al. (Frontiers in Microbiology, 2023)
In order to investigate the effects of dietary probiotics supplementation on laying performance, egg quality, serum hormone levels, immunity, antioxidant, and gut microbiota of layers at different laying stages, a total of 168 Tianfu green shell laying hens (28-day-old) were randomly divided into 2 treatments: a non-supplemented control diet (NC), and diet supplemented with 10 g/kg of probiotics, respectively. Each treatment had 6 replicates with 14 hens per replicate. The feeding trial lasted for 54 weeks. The results showed that the supplementation of probiotics significantly increased the average egg weight, improved egg quality (p<0.05) and ovarian development. Meanwhile, probiotics increased the serum hormone levels of E2 and FSH, and antioxidant indices T-AOC and T-SOD (p<0.05) of laying hens at different laying stages (p<0.05), decreased the expression of proinflammatory factors including IL-1, IL-6 and TNF-α (p<0.05). Furthermore, using 16S rRNA sequencing, we observed that the addition of probiotics increased the distribution of Firmicutes, Bacteroidota and Synergistota at early laying period. Meanwhile, Bacteroidota, Actinobacteriota, Verrucomicrobiota and Deferribacterota showed an increasing trend at the peak of egg production. The relative abundance of Firmicutes, Desulfobacterota and Actinobacteriota were significantly increased at the late laying period. Moreover, PICRUSt2 and BugBase analysis revealed that at the late laying period, the probiotics supplementation not only enriched many significant gene clusters of the metabolism of terpenoids and polyketide, genetic information processing, enzyme families, translation, transcription, replication and repair, and nucleotide metabolism, but also decreased the proportion of potential pathogenic bacteria. To sum up, these data show that the addition of probiotics not only improves the performance, egg quality, ovarian development and immune function of laying hens at different laying period, but also improves the gut microbiota of layers, thus enhances production efficiency.